New Geochemical and Mineralogical Data on Rocks and Ores of the NE Flank of the Oktyabr’skoe Deposit (Norilsk Area) and a View on Their Origin - Nadezhda Krivolutskaya; Yana Bychkova; Bronislav Gongalsky; Irina Kubrakova; Oksana Tyutyunnik; Elena Dekunova; Vladimir Taskaev (Minerals, 2020)
The Oktyabr’skoe deposit in the Norilsk ore district is the largest platinum-copper-nickel deposit in the world. It contains a huge main orebody (2.4 km3) of massive sulfide ores and some smaller sulfide bodies. Almost all publications on this deposit are devoted to the main orebody. However, to solve the problems of the deposit genesis, it is necessary to take into account the geological structure of the entire area and the composition of all orebodies. For the first time we present data on the inner structure, geochemical and mineralogical characteristics of the intrusive body, and related the disseminated and massive sulfide ores (orebody number C-5) in the northeastern flank of the deposit. The intrusion studied in the core of the borehole RG-2 consists of several horizons including the following rock varieties (from bottom to top): olivine gabbro-dolerites, taxitic gabbro-dolerites, picritic gabbro-dolerites, troctolites, olivine-free gabbro-dolerites, ferrogabbro, and leucogabbro. The intrusion shows a strong differentiated inner structure where high-Mg rocks (up to 25 wt.% MgO troctolites and picritic gabbro-dolerites) in the bottom are associated with low-Mg rocks (6–7 wt.%, gabbro-dolerites, leucogabbro, ferrogabbro) without intermediate differentiated members (8–12 wt.% MgO olivine gabbro-dolerites). Rocks are characterized by low TiO2 content (≤1 wt.%). Taxitic gabbro-dolerites, picritic gabbro-dolerites, and troctolites contain disseminated sulfide chalcopyrite-pyrrhotite mineralization (32 m thick). Cu and Ni concentrations reach up 0.74 and 0.77 wt.%, respectively. Massive ores (27 m) occur in the bottom part of the intrusion. The ores consist of pentlandite, chalcopyrite and pyrrhotite, the latter mineral dominates. Their chemical composition is stable: Cu/Ni ~1, Pd/Pt varies from 5 to 6. The C-5 orebody is similar to the C-3 orebody in terms of mineral and chemical compositions, and differ from the nearby the C-4 orebody which is characterized by a Cu/Ni ratio changing from 5 to 8. On the basis ...